THE IMPORTANCE OF FINANCIAL MONITORING AND MEASURES TAKEN TO COUNTER THE LAUNDERING OF INCOME (Conferencea, 2023)
This article discusses the definition of financial monitoring, which resulted in the emergence of the anti-money laundering system. The purpose of this article is to analyze the importance of financial monitoring and measures taken to counter the legalization of proceeds from crime and the financing of terrorism.